NAMING SYSTEMS AND CLAN SURNAMES AMONG THE HADHRAMI ARAB COMMUNITY IN PASAR KLIWON, SURAKARTA: AN ANTHROPOLOGICAL LINGUISTICS STUDY: NIẒĀM AL-TASMIYAH WA ASMĀ’ AL-ALQĀB LADĀ AL-‘ARAB AL-ḤAḌRAMIYYĪN FĪ BĀSĀR KLIWUN SŪRAKARTĀ: DIRĀSAH LISĀNIYYAH ANTRŪBŪLŪJIYYAH - Dita Kafaabillah; Muhammad Ridwan (ALLAIS Journal of Arabic Language and Literature, 2025)
Clan surnames are linguistic forms produced through long cultural processes. This study examines clan surnames of the Hadhrami Arab community in Pasar Kliwon, Surakarta, using a morphemic approach. The analysis categorizes clan surnames based on the number of constituent elements and patterns of morphological formation (wazn). In addition, this study investigates the clan naming system, focusing on naming practices and degrees of semantic opacity. Data were collected using elicitation-based interviews with community informants. The analysis employed distributional analysis through immediate constituent segmentation and referential analysis to identify linguistic patterns and their determining factors. The findings show that Hadhrami clan surnames display systematic morphological patterns that reflect both Arabic linguistic traditions and the cultural framework of the community. Understanding these clan surnames provides important insights into the cultural patterns of the Hadhrami Arab descendants in Pasar Kliwon, Surakarta.